Review Manufacturing Process of Aluminium Scrap Casting - Hasanudin, Abdul; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
This research examines various approaches in improving the quality and efficiency of the aluminium recycling process, focusing on the effect of waste type, casting method, and process parameters on the mechanical properties of the resulting product. Several studies have shown that the type of aluminium waste, such as pistons and cans, affects the hardness of the final product, while non-conventional cooling media such as coconut milk water can produce a more homogeneous microstructure. In addition, casting methods such as centrifugal casting are superior to sand casting in producing tighter microstructure and better mechanical quality. The addition of elemental tin (Sn) to recycled aluminium has also been shown to improve hardness and wear resistance, making it more suitable for severe applications. Controlling the casting temperature and controlling porosity are also important factors in obtaining products with optimum mechanical strength. While these results are promising, further research is needed to optimise cost efficiency, environmental impact and sustainability in the aluminium recycling process.